CARBON NANOTUBES–IONIC LIQUID GEL. CHARACTERIZATION AND APPLICATION TO PSEUDOEPHEDRINE AND CHLORPHENIRAMINE DETERMINATION IN PHARMACEUTICALS - Pérez-Ortiz, M.; Pizarro, P.; Álvarez-Lueje, A. (Journal of the Chilean Chemical Society, 2019)
A multi-walled carbon nanotube (MWCNT)-ionic liquid (IL) film-modified glassy carbon electrode (GCE) was constructed for the determination of pseudoephedrine (PE) and chlorpheniramine (CP) by differential pulse voltammetry (DPV). The MWCNT-IL film has shown an obvious electrocatalytic activity towards oxidation of PE and CP, since it increases the electroactive area, facilitates the electron transfer and significantly enhances the oxidation peak current of both. Also a synergistic effect between MWCNT and IL was detected; it improves the conductivity, resulting in a better response, thus the modified electrode presented higher sensitivity. Under the optimum conditions, the oxidation peak currents were linearly proportional to the concentration in the range from 40.3 to 161.3 μg/mL for PE and from 0.39 μg/mL to 27.4 μg/mL for CP. Detection limits were 32.4 μg/mL with 180 s accumulation for PE and 0.11 μg/mL with 240 s accumulation for CP. Finally, the proposed sensitive and simple electrochemical method was successfully applied to PE and CP determination in a pharmaceutical formulation, and recoveries were acceptable.